2011
DOI: 10.4061/2011/867341
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Perceptions of Clinical Fall Prevention Programs: A Qualitative Study

Abstract: Objective. To investigate motivational factors and barriers to participating in fall risk assessment and management programs among diverse, low-income, community-dwelling older adults who had experienced a fall. Methods. Face-to-face interviews with 20 elderly who had accepted and 19 who had not accepted an invitation to an assessment by one of two fall prevention programs. Interviews covered healthy aging, core values, attributions/consequences of the fall, and barriers/benefits of fall prevention strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 21 publications
4
35
0
2
Order By: Relevance
“…The older adult participants in this study often reported negative feelings such as self-blame, embarrassment, depression and sadness, suggesting that they attributed falling to their own shortcomings and personal factors rather than extrinsic factors, similar to findings in a previous study (Calhoun et al, 2011). Older adults who experience multiple falls often have decreased levels of self-esteem and motivation to participate in daily activities, which are also risk factors for depression (Fiske et al, 2009;Murphy et al, 2002).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The older adult participants in this study often reported negative feelings such as self-blame, embarrassment, depression and sadness, suggesting that they attributed falling to their own shortcomings and personal factors rather than extrinsic factors, similar to findings in a previous study (Calhoun et al, 2011). Older adults who experience multiple falls often have decreased levels of self-esteem and motivation to participate in daily activities, which are also risk factors for depression (Fiske et al, 2009;Murphy et al, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…Participant perceptions of their need for information are another important factor in the success of fall prevention programs (Calhoun et al, 2011). Since many of the older adult participants in this study expressed a strong desire to maintain their independence, addressing this need might help them more readily accept fall-related services and adhere to recommendations to prevent future falls.…”
Section: Discussionmentioning
confidence: 98%
“…5,6 Studies have focused on patients' perspectives of physiotherapy treatment and outcomes, but not on patients' experience of assessments. [7][8][9] Our study therefore aimed to explore the perspectives of both physiotherapists and patients on the use of biomechanics technology in managing balance and mobility impairments after stroke.…”
Section: Ré Sumémentioning
confidence: 99%
“…Die Studien zeigen auf, dass ältere Menschen besser aufgeklärt werden und mehr über die Gründe für ihr Sturzrisiko erfahren wollen (Carroll et al, 2010). Sie nehmen insbesondere dann an Sturzpräventionsprogrammen teil, wenn diese ihre Selbstständigkeit, Gesundheit, Autonomie, eigene Entscheidungen zu treffen und soziale Kontaktmöglichkeiten fokussieren (Calhoun et al, 2011;Carroll et al, 2010;Bunn et al, 2008;Hughes et al, 2008;Yardley et al, 2006a;McInnes, & Askie, 2004;Salkeld et al, 2000).…”
Section: Klientenzentrierte Endpunkteunclassified
“…Dazu müssen den Betroffenen ausreichende und verständliche Informationen zur Verfügung gestellt werden. Die Möglichkeit, zwischen unterschiedlichen Sturzpräventionsprogrammen auswählen zu können, wird von älteren Menschen sehr geschätzt (Haines, & McPhail, 2011 (Bunn et al, 2008;Salkeld et al, 2000;Calhoun et al, 2011;Hughes et al, 2008;Yardley et al, 2006a;Calhoun et al, 2011;McInnes, & Askie, 2004). …”
Section: Evidenzlageunclassified